2018
DOI: 10.1002/slct.201800960
|View full text |Cite
|
Sign up to set email alerts
|

Domino Oxidative Cyclization for the One‐Pot Synthesis of Pyrrolo[1, 2‐a]quinoxaline Derivatives

Abstract: An oxidative cyclization of 1‐(2‐aminophenyl)pyrrole with styrenes has been developed for the synthesis of pyrrolo[1, 2‐a]quinoxaline derivatives using I2/2‐iodoxybenzoic acid (IBX) in DMSO as an effective oxidant. I2 is found to catalyze effectively the oxidative cyclization of phenylacetylene and ethyl benzoylacetate with 1‐(2‐aminophenyl)pyrrole even in the absence of IBX to generate pyrrolo[1, 2‐a]quinoxaline derivatives under metal‐free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…When phenylglyoxal monohydrate was examined, the corresponding 4-benzoyl pyrrolo[1,2-α]quinoxaline was produced in an excellent yield ( 51 ). 19 a ,31 It is particularly noteworthy that both formalin and paraformaldehyde could be utilized as one-carbon synthons in our developed method ( 52 ). Compared to the previous one-carbon synthons such as DMF, DMSO, and PEG-400 in this transformation, 22,32 our method provides more practical and atom-efficient routes for the pyrrolo[1,2-α]quinoxaline core.…”
Section: Resultsmentioning
confidence: 99%
“…When phenylglyoxal monohydrate was examined, the corresponding 4-benzoyl pyrrolo[1,2-α]quinoxaline was produced in an excellent yield ( 51 ). 19 a ,31 It is particularly noteworthy that both formalin and paraformaldehyde could be utilized as one-carbon synthons in our developed method ( 52 ). Compared to the previous one-carbon synthons such as DMF, DMSO, and PEG-400 in this transformation, 22,32 our method provides more practical and atom-efficient routes for the pyrrolo[1,2-α]quinoxaline core.…”
Section: Resultsmentioning
confidence: 99%
“…13 C-NMR (CDCl3, 100 MHz): δ 164. 7,143.5,136.9,133.7,131.8,130.5,130.4,129.9,129.6,129.5,127.5,127.2,123.1,118.3,115.7,113.7,109.2,59.6,14.3,12.1. HRMS Anal.Calcd.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some publications indicated the use of transition metals, and others discussed metal-free reaction conditions (Scheme 1, reaction a). [4][5][6][7][8][9][10] According to the literature, the same procedures utilized in synthesizing 5x limit the pyrrole ring derivatization. Thus, new approaches for determining distinct functional groups in the 5y and quinoxaline skeletons could significantly contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Reddy et al demonstrated a highly efficient metal-free one-pot domino oxidative cyclization approach for the construction of several pyrrolo[1,2- a ]quinoxaline derivatives from alkenes and alkynes ( Scheme 30 ). 103 With the help of I 2 as the catalyst and 2-iodoxybenzoic acid (IBX) as the oxidant, the treatment of alkenes 59 with 2-(1 H -pyrrol-1-yl)aniline 90 was found to take place in DMSO to deliver the desired products 91 in good yield. A variety of electron-donating and electron-withdrawing substituents present on the aryl ring of alkenes smoothly participated in this reaction.…”
Section: Synthesis Of Fused Quinoxalines Based On Metal-free Two-comp...mentioning
confidence: 99%